2009
DOI: 10.1073/pnas.0812687106
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking doublecortin and doublecortin-like kinase 2 display altered hippocampal neuronal maturation and spontaneous seizures

Abstract: Mutations in doublecortin (DCX) are associated with intractable epilepsy in humans, due to a severe disorganization of the neocortex and hippocampus known as classical lissencephaly. However, the basis of the epilepsy in lissencephaly remains unclear. To address potential functional redundancy with murin Dcx, we targeted one of the closest homologues, doublecortin-like kinase 2 (Dclk2). Here, we report that Dcx; Dclk2-null mice display frequent spontaneous seizures that originate in the hippocampus, with most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 27 publications
1
83
0
1
Order By: Relevance
“…The convergence of these features in a mouse model could have significant consequences for circuit information processing and/or contribute to the generation of pathological network excitability associated with type I lissencephaly. A number of genetically based animal models of MCD have been developed, and most show robust hyperexcitability and/or spontaneous seizures (Wenzel et al, 2001;Kellinghaus et al 2004;Patel et al, 2004;Kwon et al, 2006;Harrington et al, 2007;Patrylo and Willingham, 2007;Nosten-Bertrand et al, 2008;Greenwood et al, 2009;Kerjan et al, 2009). When synaptic mechanisms have been investigated, these studies have typically reported postsynaptic alterations in glutamatergic excitatory Auerbach et al, 2011;Bateup et al, 2011;Luikart et al, 2011) or GABAergic inhibitory currents (Trotter et al, 2006;Ackman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The convergence of these features in a mouse model could have significant consequences for circuit information processing and/or contribute to the generation of pathological network excitability associated with type I lissencephaly. A number of genetically based animal models of MCD have been developed, and most show robust hyperexcitability and/or spontaneous seizures (Wenzel et al, 2001;Kellinghaus et al 2004;Patel et al, 2004;Kwon et al, 2006;Harrington et al, 2007;Patrylo and Willingham, 2007;Nosten-Bertrand et al, 2008;Greenwood et al, 2009;Kerjan et al, 2009). When synaptic mechanisms have been investigated, these studies have typically reported postsynaptic alterations in glutamatergic excitatory Auerbach et al, 2011;Bateup et al, 2011;Luikart et al, 2011) or GABAergic inhibitory currents (Trotter et al, 2006;Ackman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The cingulate cortex was also affected in contrast to Dcx and Dclk single KO mice, which show no apparent neocortical defects [108]. Double mutants of Dcx and Dclk2 have also been generated, however in this case the hippocampus is the most affected structure [112].…”
Section: 212bmentioning
confidence: 99%
“…Sox 2 [27][28][29] and COUP transcription factor 1 (Couptf1), also known as Nr2f2, [26,30] were chosen as markers for cluster 1, and in situ hybridization for both genes showed their expression restricted to the ventricular zone, as expected ( Figure 4A-H). For cluster 2, in situ hybridization for Doublecortin like kinase 2 (Dclk2) and Sox11 [31,32] delineated a narrow region immediately ventral to the ventricular zone, matching the expected location of this cluster ( Figure 4I-L). In situ hybridization for cluster 3 gene Melanoma antigen family D1 (Maged1) labeled an area immediately dorsal to the Gap43 signal, also matching the expected spatial location of this cluster ( Figure 4Q-T).…”
Section: Spatial Pattern Validation Of Medial Ganglionic Eminence Tramentioning
confidence: 99%